Preparation process and properties of polyurethane/phosphogypsum-modified asphalt and its mixtures - Jinshun Xue; Yu Yang; Junfeng Li; Wei Zhao; Yuanyuan Wang (PLoS ONE, 2025)
The preparation process parameters and composition of polyurethane/phosphogypsum-modified asphalt were studied to achieve comprehensive utilization of phosphogypsum and reduce asphalt pavement costs while ensuring performance compliance. Additionally, the aging resistances of the modified asphalt and its mixtures were investigated. The results showed that the order of the influence of the different preparation process parameters on the performance of modified asphalt is preparation temperature, storage time, reaction time, and shear rate. The optimal preparation process parameters, namely 130°C preparation temperature, 2000 rpm shear rate, 1.5 h reaction time, and 1.0 h storage time, of polyurethane/phosphogypsum composite-modified asphalt are recommended based on the experimental results. Polyurethane/phosphogypsum-modified asphalt with 3% component A, 1% component B, 5% phosphogypsum, and 0.5% coupling agent exhibited superior performance. The average change rates of the modified asphalt properties after short- and long-term aging were 23.9% and 42.2% lower than those of the base asphalt, respectively. Finally, the modified asphalt mixture exhibited average change rates of 8.7% and 18.2% in high-temperature performance after short- and long-term aging, respectively, which were significantly lower than the change rates of 15.3% and 23.5% observed in the base asphalt mixture.